One-dimensional dispersion of conservative tracer materials in trickling filter in case of rhombic arrangement - Unlu, A.; Sekerdag, N. (My University, 1993)
This paper deals with the dispersion phenomenon of conservative tracer materials. Rhombic arrangements is taken into account in trickling filters and a nonuniform flow condition is held. A general differential equation is derived and applied to describe the flow over a spherical-jet chain. A computer aided solution method is presented. The calculation of the dispersion coefficients by means of this approach is shown by examples for flow conditions through trickling filters. (English summary)
Damlatmali filitrelerde rombik dizilisli duzen icin korunan maddelerin dispersiyonu
Keywords: Dispersion; Filters; Trickling Filters